ANALISIS PEMASARAN IKAN LELE SANGKURIANG DI KABUPATEN OKU TIMUR - Hariyono (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research were to : (1) To know how the marketing channel of sangkuriang catfish in East OKU, (2) to know the kentungan obtained by each marketing institution of sangkuriang catfish in East OKU, (3) Analyze how efficiency, marketing margin , Farmer share on each marketing channel of sangkuriang catfish in East OKU Regency. This research was conducted in two sub-districts, Belitang and Buay Madang Timur of OKU Timur Regency, the selection of research location was done purposively with the consideration that both sub-districts are one of production centers of sangkuriang catfish and from various types of consumption fish produced. This research was conducted in March - April 2014. This research found that marketing channel of catfish sangkuriang up to the existing consumer in East OKU there are 3 channel that is Channel I (cultivation of catfish sangkuriang to consumer) Channel II (Cultivator of catfish sangkuriang Gatherer Consumer Retailer Dealer) Channel III (Cultivators of catfish sangkuriang Large Traders of Consumers). The biggest marketing margin accepted by the marketing institution is the big trader that is Rp. 4.900, - / kg then the collector is Rp.3.224, - / kg while the retailer is only Rp.1.717, - / kg while the highest farmer share on channel I where the farmer sells directly to the consumer and is not charged to marketing costs. Sangkuriang catfish marketing channel in East OKU district where channel I (direct producer to consumer) is the best marketing channel. This is caused by the channel I lack of additional marketing costs.